A Simplified View about the Fuegian Andes and the Complex Folding of the Mesozoic and Early Tertiary Layers - Acevedo, Rogelio Daniel
The arch described by the Patagonian orogenic belt in Tierra del Fuego and the acute folding of the Mesozoic and earliest Tertiary strata are not two independent phenomena. The search for the causes that have produced these two structural features, arc and folding, has to take into consideration the undeniable fact that nature does not follows a strict one cause-one effect relationship as in physical or chemical experiments, but it is more a relation of groups of causes and groups of effects. Even the possibility of a convergence of multiple causes must be taken in account in this multiple game. The Fuegian arc and the building of a range with an E-W jointing orientation on one side the straight Patagonian Cordillera (N-S direction) and on the other side it joins the great arc that encloses the Drake Passage and the Scotia Sea.The shift was in a non-perpendicular angle to the N-S Cordillera, that is SW or WSW in direction: a under-thrusting or deep rigid movement forward worked in the orogenic warping, perhaps contributing then to the overturning of the Mesozoic strata. Last but not least, the simpler conception of the idea that the Magallanes-Fagnano fault is just an inner transcurrent fault of the South American plate is approached here. Fil: Acevedo, Rogelio Daniel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina